Spontaneous Aortic Dissection Limited to the Sinus of Valsalva: Report of Two Cases - Maryam Nabati; Babak Bagheri; Samira Eslami; Razhan Piran (Journal of Tehran University Heart Center, 2016)
Dissection of the sinus of Valsalva is a rare and life-threatening event. It often occurs during percutaneous coronary intervention in the right coronary artery (RCA). Dissection flap usually involves the RCA and the right sinus of Valsalva. Here we report two extremely rare cases of spontaneous dissection limited to the non-coronary sinus of Valsalva, causing severe aortic valve regurgitation: a male aged 51 years presenting with back pain, weakness, and presyncope and another male aged 71 years presenting with orthopnea and weakness. The dissection was found by transesophageal echocardiography. Surgical treatment was successful for both patients.